2021
DOI: 10.21203/rs.3.rs-262284/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitigating Environmental Degradation With Institutional Quality and Foreign Direct Investment (FDI): New Evidence From Asymmetric Approach

Abstract: Chile is currently rated among the performing countries towards the achievement of the global goals of reducing carbon emission. It is on recorded that Chile as a country has moved from highly insufficient to insufficient and still working towards conforming to the recommend the region of 20C in quest of controlling climate change through carbon emission reduction. From this development, it is essential to investigate on the country’s strategies in achieving this success and equally make recommendation for oth… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It is instructive to note that foreign direct investment shocks may be expected to have different effects on the carbon emissions of countries. Recent empirical studies have shown that the effects of foreign direct investment could be asymmetric (Gao et al 2022;Udemba 2021). In other words, positive foreign direct investment shocks do not have an equivalent negative foreign direct investment shocks.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…It is instructive to note that foreign direct investment shocks may be expected to have different effects on the carbon emissions of countries. Recent empirical studies have shown that the effects of foreign direct investment could be asymmetric (Gao et al 2022;Udemba 2021). In other words, positive foreign direct investment shocks do not have an equivalent negative foreign direct investment shocks.…”
Section: Theoretical Frameworkmentioning
confidence: 99%